PENDIDIKAN KARAKTER DALAM BUKU SIRAH NABI MUHAMMAD KARYA AL-HAFIZH ADZ-DZAHABI - Muhilda, Vena (Program Studi Pendidikan Agama Islam, Fakultas Agama Islam UNISMA Bekasi, 2023)
This study aims to determine Character Education in the book Sirah Nabi Muhammad by Al-Hafizh AdzDzahabi. The background of this research is the lack of good character caused by daily habits that cause negative characters for students, both from the family, the surrounding environment, playmates, and technology, the lack of education in forming character because education prioritizes and develops intellectual intelligence rather than improve character for students. As well as the many shows on social media and television that do not educate so they cannot form character. This research is a type of qualitative research using the library research approach. The data analysis method used in this research is descriptive method and library method.